THE ELEMENTS AND OXIDE CONTENT OF THE CHEMICAL COMPOSITION OF THE FELDSPAR - Jumaeva, Dilnoza; Zaripbaev, Kunkhoja; Maxmudov, Firuz (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In this article, the results of purifying feldspar from foreign compounds in its composition through the study of its chemical composition are described through the quantitative indicators of oxides and elements in the analysis of its chemical composition. Based on the obtained results, the mineralogical analysis of feldspar was studied, and it was substantiated that the purity level of silicon dioxide is higher in value compared to other elements.